Building Asian climate change scenario by multi‐regional climate models ensemble. Part I: surface air temperature. (5th February 2016) - Tang, Jianping; Li, Qian; Wang, Shuyu; Lee, Dong‐Kyou; Hui, Pinhong; Niu, Xiaorui; Gutowski, William J.; Dairaku, Koji; McGregor, John; Katzfey, Jack; Gao, Xuejie; Wu, Jia; et al.
ABSTRACT: Under the Asia‐Pacific Network for Global Change (APN) project 'Building Asian Climate Change Scenarios by Multi‐Regional Climate Models Ensemble' (RMIP III, Regional Model Intercomparision Project), the simulation results of eight regional climate models (RCMs) and two fine‐resolution global climate models are validated for reproducibility of the current surface air temperature climatology (1981–2000), and are used to generate surface air future temperature projections (2041–2060) over the CORDEX‐EA (A Coordinated Regional climate Downscaling Experiment‐East Asia) domain. Four ensemble methods, namely, the equal weighting, the weighted mean, the reliability ensemble averaging, and the performance‐based ensemble averaging, are employed to generate the multi‐model projection of regional climate change over the region. The results show that the regional temperature ensembles of the present climate obtained from all four methods can outperform a single RCM result in aspects of the spatial distribution as well as the seasonal variation over East Asia. The four ensemble methods are then used to project the regional temperature climatology under the IPCC emission scenario of A1B for 2041–2060. Compared with the control climate of 1981–2000, the annual mean temperature of the future climate (2041–2060) increases 1–2 °C in low latitude areas and 2–3 °C in middle–high latitude areas over Asia.